IMPLEMENTASI KEBIJAKAN PENDIDIKAN KARAKTER DALAM MEMINIMALISASI KENAKALAN REMAJA - Asnani Asnani; Mislia Mislia; Susiana Susiana (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
The role of education in character development is very strategic because to shape the character of effective students it can only be done through education, in this case the school residents (school principals,teacher, employee, and student) has a very important role in the development of character and moral values of students. Therefore, the Principal as managers and leaders are responsible for translating and implement character education policies in order to shape the character of students in this case to minimize juvenile delinquency. This study aims to analyze the character education policy implementation in minimizing adolescence. The research method used in this study is a qualitative method with the type of descriptive research study approach documents / texts.